Por entre percursos e narrativas: a experiência formativa dos deslocamentos urbanos de trabalhadores em Belo Horizonte - Claudio Marcio Oliveira (2011)
This study approaches the formative experiences of workers' urban daily travels throughout the metropolitan area of Belo Horizonte. As a fundamental assumption, it is pointed out that urban trips are not just a hiatus or a simple functional act but subjective processes and experiences taken by people moving around the city. Considering this and to carry out this research, Walter Benjamins concepts of Comunicable Experience (Erfahrung) and Isolated Experience (Erlebnis) were taken to understand the building process of sensibilities in the citys networks as the first concept keeps an inseparable link with the narratives produced by the researched individuals. The empirical material consisted of three different types of sources. Firstly, it was taken a participatory action research on urban travels of four workers and residents of Belo Horizonte, especially in the Barreiro region, mphasizing the act of walking and the daily use of public transport. Secondly, it was analyzed two media means used inside the buses: the Journal of the Bus and the Timetables, which were taken as being representations on how bus service users build a sense of belonging with the city. Thirdly, semi-structured interviews were taken and life history of individuals were sought as evidence by their relations with the city over the years and their perceptions of daily travels by the city. Thus, the experience of moving around in the city was analyzed based on the following considerations: the relations that individuals establish with the citys multiple times and rhythms; the uses and perceptions of buses' spaces; the relationships established by individuals with strangers during urban daily travels; the body notion, its place, and sensitivities in urban daily travels; the processes of transforming behavior more ethical and the users´ bodies by the Journal of the Bus; and finally, the city and life desires drawn up by the researched individuals. The researched workers´ experiences have raised a set of guidelines for reflection and action. Among them, it is highlighted: the need to address the issue of speed as an issue of public concern along with social processes; a questioning situation on the functionality criteria that guide the supplying public transport in Belo Horizonte; and, especially, the need of questioning the aesthetic dimension of urban daily travels which is a key condition for building aculture on meetings that could materialize the Right to the City to its inhabitants